Putting the cat before the wildlife: Exploring cat owners' beliefs about cat containment as predictors of owner behavior. Issue 10 (27th July 2021) - van Eeden, Lily M.; Hames, Fern; Faulkner, Richard; Geschke, Andrew; Squires, Zoe E.; McLeod, Emily M.
Abstract: Free‐roaming domestic cats pose risks to wildlife, domestic animals, humans, and importantly, the cats themselves. Behavior change campaigns that seek to minimize these risks by increasing cat containment require an understanding of the factors that predict cat owners' containment behaviors. We conducted an online survey in Victoria, Australia ( N = 1, 024) to identify cat owners' ( N = 220) behaviors in containing their cats, explore beliefs and attitudes that predict containment behavior, and compare attitudes about cat containment with respondents that do not own cats ( N = 804). We found that 53% of cat owning respondents do not allow any roaming. These respondents were more likely to hold concerns about risks to cats' safety while roaming and less likely to perceive that cats have a right to roam. Concern about impacts to wildlife was not a significant predictor of containment behavior. Expectations that cat owners should manage cats' roaming behavior was a social norm among cat owners and other respondents, and cat containers were more likely to indicate that they would try to change behaviors of their peers that they perceived to be harmful to the environment. Cat containment campaigns could be improved by appealing to owners' concerns about cat well‐being, engaging respected messengers that align with these concerns, including owners who already contain their cats.